2019
DOI: 10.1111/psyp.13397
|View full text |Cite
|
Sign up to set email alerts
|

Generalization of appetitive conditioned responses

Abstract: A stimulus (conditioned stimulus, CS) associated with an appetitive unconditioned stimulus (US) acquires positive properties and elicits appetitive conditioned responses (CR). Such associative learning has been examined extensively in animals with food as the US, and results are used to explain psychopathologies (e.g., substance‐related disorders or obesity). Human studies on appetitive conditioning exist, too, but we still know little about generalization processes. Understanding these processes may explain w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
4
6
1
Order By: Relevance
“…Moreover, the verbal conditioned responses demonstrated that the G75-CTX and the G50-CTX were more anxiogenic than the CTX−, whereas the G25-CXT was rated as safe as the safety context. These results replicate previous findings [36][37][38][39] indicating that the generalization context with equal properties of anxiety and safety context was reported as threatening. Furthermore, we could extend these results as well as results on fear generalization [18][19][20]22] by showing that the Fig.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Moreover, the verbal conditioned responses demonstrated that the G75-CTX and the G50-CTX were more anxiogenic than the CTX−, whereas the G25-CXT was rated as safe as the safety context. These results replicate previous findings [36][37][38][39] indicating that the generalization context with equal properties of anxiety and safety context was reported as threatening. Furthermore, we could extend these results as well as results on fear generalization [18][19][20]22] by showing that the Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Conceivably, high anxiety sensitive individuals would have shown both a linear generalization trend and startle potentiation to the generalization contexts as compared to the safety context. Although simple contrasts for physiological responses between generalization contexts and safety context is in contrast to the verbal reports, it is in line with previous studies in which the physiological conditioned anxiety was not generalized to the G50-CTX [36][37][38][39]. Notably, such safety generalization is also evident in the literature of cue conditioning, in which it has been found that the equal mix of the threat and safety signal does not elicit strong fear responses in healthy individuals [18][19][20]22].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Peelen (2015, 2017) also reported a generalization of associations between naturalistic visual stimuli and reward to objects of the same category (e.g., cars). More recently, Andreatta and Pauli (2019) showed that appetitive conditioned responses transferred to stimuli perceptually related to signals paired with food consumption in a prior acquisition phase. However, studies about the generalization of stimulus-reward associations mainly focused on perceptual cues.…”
mentioning
confidence: 99%